Microelectronics - Whitaker, Jerry C. ([S.l.] : CRC Press, 2000)
Advances In recent decades have created virtually free computing power, available to a great cross-section of society. This has lead to a rocketing demand for microelectronics in all sectors of consumer, industrial, and military markets. To keep pace, the engineers need a resource that provides broad, fundamental knowledge of the field's myriad technologies and applications. Microelectronics is that resource. Offering information in a concise, easy-to-read format, it presents the fundamentals of microelectronics, a summary of the current state of electronics, and the innovative directions it is taking. Contributions from top experts provide an understanding of the technologies shaping the microelectronics industry and how these technologies affect the end-use of microelectronic devices. Microelectronics offers a convenient and complete reference to microelectronics applications. It instills a sense of the future of microelectronics technology and the likely growth in its applications. It is a "must-have" for engineers in this quickly changing, consumer-driven field.